A priori analysis as a part of teachers’ lesson planning - Nováková, Hana (Scientia in educatione, 2020)
The paper focuses on a research in the domain of didactical engineering as defined and described in the Theory of Didactical Situations. The research enquires into a priori analysis of didactical situations and its relationship to the process of lesson planning by primary and secondary in-service and pre-service mathematics teachers. The paper describes an experiment designed and carried out with the aim of pinpointing and giving account of the possible causes of differences between a priori analysis and teachers’ lesson plans. It also shows and explains differences between primary, secondary and pre-service mathematics teachers.